Interpersonal Meaning in Netanyahu’s Speech - Arif Firmansah (University of Kuningan, 2015)
This study investigates how the interpersonal meaning is realized in the speech of Israeli Prime Minister Benjamin Netanyahu. This study aimed to uncover (1) the mood structure which realized in Netanyahu‘s speech of Iran and Palestine and (2) To what extent the difference in field determine the interpersonal metafunction of the speaker. This study is largely qualitative but in order to answer those research questions, this study will be assisted by some descriptive quantification to observe the trend in the interpersonal meaning of the speaker. It applies Hallidayan theory of Systemic Functional Grammar (SFG) in analyzing the research data. The data were taken from the websites which are readily accessible to the public. Two different transcribed speeches are discovered to extract the data which are needed to investigate the interpersonal meaning. Subject, Finite and Modality are the main tools to realize the interpersonal meaning of Netanyahu in his speech. It can be realized by discovering the use of those parts in his speech in different issue and occasion. It is found that Netanyahu‘s interpersonal meaning is realized through the placement of Subject and the utilization of Finite, Modality and Mood Adjuncts. It is also found that the differences of the field influence the interpersonal meaning of the speaker through the comparison of subject and finite. The findings in this present study are expected to be useful for some purposes in the future.Keywords: Interpersonal meaning, mood, modality.